2019
DOI: 10.1186/s40478-019-0714-6
|View full text |Cite
|
Sign up to set email alerts
|

Delta-24-RGD combined with radiotherapy exerts a potent antitumor effect in diffuse intrinsic pontine glioma and pediatric high grade glioma models

Abstract: Pediatric high grade gliomas (pHGG), including diffuse intrinsic pontine gliomas (DIPGs), are aggressive tumors with a dismal outcome. Radiotherapy (RT) is part of the standard of care of these tumors; however, radiotherapy only leads to a transient clinical improvement. Delta-24-RGD is a genetically engineered tumor-selective adenovirus that has shown safety and clinical efficacy in adults with recurrent gliomas. In this work, we evaluated the feasibility, safety and therapeutic efficacy of Delta-24-RGD in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…Intratumoral administration of DNX-2401 was safe in mice and resulted in a significant increase of survival rate in both immunodeficient and immunocompetent models of pHGG and DIPG 61. The same group further showed that DNX-2401 treatment downregulated DNA damage repair proteins and when combined with radiotherapy mediated a synergistic anti-glioma effect in mouse models of pHGG and DIPG 62. Currently, a Phase I trial of DNX-2401 for newly diagnosed DIPG is ongoing in Spain (NCT0317803263).…”
Section: Clinical Trial Of Dnx-2401 For Malignant Gliomasmentioning
confidence: 97%
“…Intratumoral administration of DNX-2401 was safe in mice and resulted in a significant increase of survival rate in both immunodeficient and immunocompetent models of pHGG and DIPG 61. The same group further showed that DNX-2401 treatment downregulated DNA damage repair proteins and when combined with radiotherapy mediated a synergistic anti-glioma effect in mouse models of pHGG and DIPG 62. Currently, a Phase I trial of DNX-2401 for newly diagnosed DIPG is ongoing in Spain (NCT0317803263).…”
Section: Clinical Trial Of Dnx-2401 For Malignant Gliomasmentioning
confidence: 97%
“…The synergy between OVs and radiotherapy has also been assessed. Recently, Martínez-Velez et al demonstrated that combining the Delta-24-RGD virus with radiotherapy resulted in a synergistic antiglioma activity in vitro and in vivo in pediatric high-grade glioma (pHGG) and diffuse intrinsic pontine glioma (DIPG) models [ 135 ]. This combined therapy increased the tumor lymphocyte infiltration post-Delta-24-RGD injection, overcoming the immune “cold” status and potentially allowing the abscopal effect triggered by the radiotherapy to take place.…”
Section: Combination Therapy In Preclinical and Clinical Settingsmentioning
confidence: 99%
“…Models using in utero electroporation to deliver PiggyBac DNA transposon plasmids expressing H3.3 K27M in neural progenitor cells have also been developed [22,23]. Marigil et al recently developed a guide-screw system based DIPG xenograft model, which allows the generation of tumors in a fast and reproducible fashion and allows to deliver the therapeutics via the same screw fixed system route [6,24,25]. Smith et al recently performed a comprehensive histopathological and molecular analysis of 37 novel patient-derived orthotopic xenograft (PDOX) models developed from pediatric brain tumor patients [26], associated datasets can be accessed at (http://pbtp.stjude.cloud).…”
Section: Preclinical Animal Models Of Dipgmentioning
confidence: 99%
“…The differentiation, maturation, activation, and proliferation of T cells are disrupted by these MDSCs, ultimately leading to T cell exhaustion and death. stand out as potential treatments due to their minimal invasiveness and comprehensive tumor-eradicating capability [6,7,25,27,34]. The DIPG microenvironment contains low levels of antigen presenting cells (APCs) and adaptive immune cells, contributing to the tumor's ability to grow undetected by the immune system [27,34,35].…”
Section: Ongoing Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation